The Effectiveness of Program Based on Fractal Geometry in Developing Nanotechnology Concepts among Mathematics Students at Faculty of Education - Al-Kamel, Ibtesam Mohammed Ahmed Abdullah; Saeed, Radman Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to know the effectiveness of a program based on fractal geometry in developing nanotechnology concepts among mathematics students at faculty of Education. The researchers used quasi- experimental approach with design of two groups (experimental and control group). The sample of this study consisted of (43) students, in the second level in Mathematics Department, at Faculty of Education, Sana’a University. They were distributed to the experimental group that consisted of (23) students and control group that consisted of (20) students. For data ware collecting by a built scale of nanotechnology concepts.The results of this study showed that there were statistically significant differences at the level of significance (α≤0.05) in the scale of nanotechnology concepts as a whole and in students’ knowledge of the concepts of nanomaterials and nanotechnology in favor of experimental group but there are no statistically significant differences in both students’ knowledge of the concept and applications of nanotechnology. In the light of the results of the study, it is recommended to exploit the interests of students in the age of technology in the educational process by including modern concepts such as fractal geometry, nanotechnology, and others, to make them open to developments of the contemporary world.